Nonlocal boundary-value problem for parabolic equations with variable coefficients - Zadorozhna, N. M.; Ptashnik, B. I. (Ukrains’kyi Matematychnyi Zhurnal, 1995)
We study the boundary-value problem for Petrovskii parabolic equations of arbitrary order with variable coefficients with conditions nonlocal in time. We establish conditions for the existence and uniqueness of a classical solution of this problem and prove metric theorems on lower bounds of small denominators appearing in the construction of a solution of the problem.